ANALYSIS OF PATIENT SATISFACTION WITH THE QUALITY OF HEALTH SERVICES - Johan Budhiana; Rakanda Putra Waliyu; Dedi Wahyudin; Waqid Sanjaya (Universitas Kusuma Husada Surakarta, 2026)
Background: Patient satisfaction is a crucial issue in the healthcare system because it reflects the quality of healthcare services. As public awareness grows, patients expect healthcare providers to deliver high-quality, safe, and patient-centered care. The purpose of this study is to analyze patient satisfaction with the quality of healthcare services.Methods: This was a descriptive study. The population consisted of all patients visiting the community health center, with a sample of 215 individuals selected using incidental sampling. Data were collected using a service quality assessment questionnaire based on a Likert scale. Data collection took place from April through May 2024. Data analysis techniques included IPA and CSI.Results: Health services are considered very important (4.76), health service performance is considered good (4.11), gap value (-0.65), suitability value (86.43), the priority indicators that need to be improved are the ability of health workers to explain patients' illnesses, the opportunity given by health workers to patients to ask questions about their illness, the ability of health workers to communicate with patients, the ability of health workers to understand patients, the willingness of health workers to provide explanations if patients do not understand their illness, and the fairness of health workers in providing services, as well as the CSI value (0.82), which is in the very satisfied category.Conclusion: Overall patient satisfaction is very high. The Sukakarya Community Health Center in Sukabumi City is expected to improve the top-priority indicators.